Assessment of the performance of ICCP, hybrid anode and sacrificial anode systems operating on concrete bridges and structures in NSW, Australia based on potential criteria - Fatemi Hamid; Cheaitani Atef (MATEC Web of Conferences)
The bulk of reinforced concrete bridges and wharves along the Australian coastline are exposed to the risk of chloride induced corrosion. For many of these structures, concrete deterioration has occurred due to chloride induced corrosion. As part of the long-term maintenance strategy for reinforced concrete bridges and structures in New South Wales, various types of corrosion protection systems were installed on bridges and wharves over the past thirty years. The majority of the early installations were impressed current cathodic protection (ICCP) systems, and in recent years, hybrid anode cathodic protection (HACP) and sacrificial anode cathodic protection (SACP) systems have increasingly been used for corrosion protection. A comprehensive performance monitoring program is in place for some of these operating corrosion protection systems based on the corrosion protection system type. The program complies with the current Australian Standard for performance monitoring, including functional checks at three-month intervals and performance testing at six-month intervals for all ICCP systems. For the sacrificial and hybrid anode systems, the program includes annual testing to obtain information related to the level of corrosion protection provided by the systems. The overall aim of the program is not only to ensure that all corrosion protection systems are monitored and maintained based on the applicable standards, but also to assess the effectiveness of various corrosion protection technologies for future implementation through the yearly system audit. This paper will summarise the performance of some of the ICCP, HACP and SACP systems operating in New South Wales, Australia. This information will be useful for asset owners who need to select the most efficient corrosion protection technology based on the expected service life of their assets.